Barriers and Facilitators for Academic Success and Social Integration of Refugee Students in Canadian and US K–12 Schools: A Meta-Synthesis - Antony-Newman, Max; Niyozov, Sarfaroz (Canadian Journal of Education / Revue canadienne de l'éducation)

(untitled) (Canadian Society for the Study of Education, 2023)
Despite the status of Canada and the United States as major destinations for refugees worldwide, school-age refugee children in their K–12 schools continue to face significant challenges. To better understand barriers and facilitators for refugee students after resettlement, we carried out a meta-synthesis of 34 peer-reviewed articles that shed light on the educational experiences of refugee students in this geographic context. Our analysis shows that refugee students face such barriers as inappropriate grade placement, deficit thinking of teachers, language barriers, lack of trauma-specific counselling, and misunderstandings in family-school communication. Nevertheless, refugee students benefit from culturally relevant curriculum and pedagogy and the availability of cultural brokers and liaisons. The key theoretical and policy implication of this meta-synthesis is the need to shift the focus from the type of refugee programs (integrated or separate) to the presence of facilitating factors that enhance the academic success and social integration of refugee students.